Gynecological morbidity prevalence correlates perceptions and health care seeking behavior among ever married women in reproductive age in the Ratnapura District. - Hemachandra, D.K.N.N (My University, 2007)
Information on socio demographic characteristics, menstrual and obstetrics histories, contraceptive use, sexual behavior, gynecological symptoms, impact of gynecological symptoms on women's day-to day life and health seeking behavior was collected using an interviewer administered, pre coded, structured questionnaire. Complete clinical examination was carried out including a gynecological examination and laboratory investigations to detect RTIs, cervical cell abnormalities, syphilis, random blood sugar and haemoglobin levels. Focus group discussions, in-depth interviews and key informant interviews were used to gather information on perceptions, consequences and healthcare seeking behavior related to gynecological morbidity. The participation rate was high (95.5 percent ). The prevalence of self reported gynecological symptoms was 62.4 percent (95 percent CI 59.7-65.1). The most common gynecological problem was pre menstrual syndrome (62.4 percent 95 present C.I. 59.4-66.1), followed by problems related to menstrual bleeding (43.1 percent , 95 percent C.I. 38.9-46.6). The prevalence of dysmenorrheal was 33.4 percent (95 present C.I. 30.2-36.7). Multivariate logistic regression models revealed statistically significant associations of irregular periods with living in the estate sector (p 23 kg/m2 (OR= 1.37) and living in estate or urban sector were significantly associated with utero-vaginal prolapse in multivariate analysis. percent The prevalence of dysparaunia was 12.4 percent (95 C.I. 10.6-14.5) arid in multivariate analysis, presence of utero-vaginal prolapse (OR=3.74), history of instrumental delivery (OR=1.99), being a young woman (age less than 35 years) (OR=1.81) and low standard of living index (OR=2.27) were significant predictors of dysparaunia